2006
DOI: 10.1172/jci29441
|View full text |Cite
|
Sign up to set email alerts
|

Misbehaving macrophages in the pathogenesis of psoriasis

Abstract: Psoriasis is a chronic inflammatory skin disease unique to humans. In this issue of the JCI, 2 studies of very different mouse models of psoriasis both report that macrophages play a key role in inducing psoriasis-like skin disease. Psoriasis is clearly a polygenic, inherited disease of uncontrolled cutaneous inflammation. The debate that currently rages in the field is whether psoriasis is a disease of autoreactive T cells or whether it reflects an intrinsic defect within the skin -or both. However, these que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 30 publications
4
97
1
Order By: Relevance
“…Studies in humans and in mouse models of psoriasis revealed also a pivotal role for macrophages and macrophage-produced cytokines in the pathogenesis of psoriasis (3)(4)(5)(6). Thus, we found that macrophages within the lesional skin are activated to become the main source of the proinflammatory cytokines such as TNF-␣ (4).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans and in mouse models of psoriasis revealed also a pivotal role for macrophages and macrophage-produced cytokines in the pathogenesis of psoriasis (3)(4)(5)(6). Thus, we found that macrophages within the lesional skin are activated to become the main source of the proinflammatory cytokines such as TNF-␣ (4).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo counterparts of M2 macrophage polarization have been observed in tissue remodelling during ontogenesis [28], chronic inflammation [29][30][31][32][33][34][35][36][37][38][39][40][41][42], cancer [9,12,16,17], bacterial [43][44][45][46][47][48][49] and parasitic [50][51][52][53] infections. Evidence has also accumulated that polarized macrophages are more than mere spectators of immunopathology [35][36][37][38][39][40][41][50][51][52].…”
Section: Activation and Adaptive Responses Of Macrophagesmentioning
confidence: 99%
“…Evidence has also accumulated that polarized macrophages are more than mere spectators of immunopathology [35][36][37][38][39][40][41][50][51][52].…”
Section: Activation and Adaptive Responses Of Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also found in a T-cell-independent mouse model, with an increase of TNF- in macrophages (Stratis et al, 2006). Based on literature data, an emerging model of psoriasis pathogenesis in humans suggests that dermal macrophages, activated by T-cell cytokines, produce large amounts of TNF-, leading to skin changes (Clark & Kupper, 2006).…”
Section: Accessory Cells (Dendritic Cells and Macrophages)mentioning
confidence: 64%